Complete mitochondrial genomes of Callospermophilus lateralis and Urocitellus richardsonii (Rodentia: Sciuridae). Issue 1 (1st January 2016) - Zhang, Leping; Huang, Yuanyuan; Storey, Kenneth B; Yu, Danna; Zhang, Jia-Yong
Abstract: The complete mitochondrial genomes of Callospermophilus lateralis and Urocitellus richardsonii (Rodentia: Sciuridae) were sequenced to analyze the gene arrangement and discuss the phylogenetic relationship of species within the Xerinae. The genomes are circular molecules of 16, 457 bp and 16, 460 bp in length, respectively, including the 37 genes typically found in other squirrels. The AT content of the overall base composition is 63.2% for both species. The length of control region for C. lateralis is 1009 bp with 62.8% AT content; the corresponding values for U. richardsonii are 1012 bp and 62.0% AT content. In BI and ML phylogenetic trees, the monophyly of the family Sciuridae and subfamilies Callosciurinae and Sciurinae are well supported, but the monophyly of Xerinae is not supported. Within the Xerinae, the relationship of ( Tamias sibiricus + ( Callospermophilus lateralis + ( Marmota himalayana + ( Urocitellus richardsonii + ( Ictidomys tridecemlineatus + ( Cynomys leucurus + Cynomys ludovicianus )))))) is well supported. However, Tamiops swinhoei (Xerinae) within the subfamily Callosciurinae is a clade sister to Dremomys rufigenis (Callosciurinae). Spermophilus dauricus (Xerinae) within subfamily Sciurinae is a sister clade to Sciurus vulgaris (Sciurinae). The monophyly of Xerinae is failed to support in this study.